Research and Development Trends of Expressway Maintenance Management Technology - Zhang, Qingsong (Asia Pacific Economic and Management Review, 2026)
Expressway safety is a crucial prerequisite for safeguarding the life and health of drivers and passengers, with maintenance management serving as its core support. To enhance the safety and sustainability of expressway maintenance management, this paper first analyzes the fundamental components, characteristics, existing problems, and corresponding countermeasures of maintenance management. Secondly, it proposes optimization measures for the safety management of expressway maintenance construction. Finally, it predicts future development trends in maintenance operations from four perspectives: management mechanisms, digital transformation, investment mechanism optimization, and full life-cycle ecologization. This study aims to provide decision-making support and technical references for expressway operating entities and maintenance personnel.